A community-based exercise intervention transitions metabolically abnormal obese adults to a metabolically healthy obese phenotype - Dalleck LC (Dove Medical Press, 2014)
Lance C Dalleck,1,3 Gary P Van Guilder,2,3 Tara B Richardson,1 Donald L Bredle,3 Jeffrey M Janot31Recreation, Exercise, and Sport Science Department, Western State Colorado University, Gunnison, CO, USA; 2Department of Health and Nutritional Sciences, South Dakota State University, Brookings, SD, USA; 3Department of Kinesiology, University of Wisconsin-Eau Claire, Eau Claire, WI, USABackground: Lower habitual physical activity and poor cardiorespiratory fitness are common features of the metabolically abnormal obese (MAO) phenotype that contribute to increased cardiovascular disease risk. The aims of the present study were to determine 1) whether community-based exercise training transitions MAO adults to metabolically healthy, and 2) whether the odds of transition to metabolically healthy were larger for obese individuals who performed higher volumes of exercise and/or experienced greater increases in fitness.Methods and results: Metabolic syndrome components were measured in 332 adults (190 women, 142 men) before and after a supervised 14-week community-based exercise program designed to reduce cardiometabolic risk factors. Obese (body mass index ≥30 kg · m2) adults with two to four metabolic syndrome components were classified as MAO, whereas those with no or one component were classified as metabolically healthy but obese (MHO). After community exercise, 27/68 (40%) MAO individuals (P<0.05) transitioned to metabolically healthy, increasing the total number of MHO persons by 73% (from 37 to 64). Compared with the lowest quartiles of relative energy expenditure and change in fitness, participants in the highest quartiles were 11.6 (95% confidence interval: 2.1–65.4; P<0.05) and 7.5 (95% confidence interval: 1.5–37.5; P<0.05) times more likely to transition from MAO to MHO, respectively.Conclusion: Community-based exercise transitions MAO adults to metabolically healthy. MAO adults who engaged in higher volumes of exercise and experienced the greatest increase in fitness were significantly more likely to become metabolically healthy. Community exercise may be an effective model for primary prevention of cardiovascular disease.Keywords: exercise, obesity, prevention, risk factors